A9.13 systemic LDL cholesterol-accumulation during experimental oa leads to increased synovial thickening, s100a8/9 production and ectopic bone formation. (31st January 2014) - de Munter, Wouter; van den Bosch, Martijn HJ; Sloetjes, Annet W; Vogl, Thomas; Roth, Johannes; van der Kraan, Peter M; van den Berg, Wim B; van Lent, Peter LEM
Abstract : Introduction: In a previous study, we showed that LDL accumulation by LDL receptor deficient mice resulted in increased ectopic bone formation during experimental osteoarthritis (OA). Furthermore, we found that S100A8/A9 proteins are crucial in mediating joint pathology during experimental OA. In the present study we investigate OA pathology and its correlation with S100A8/9 in ApoE-/- mice, which is a different model for studying effects of systemically high LDL cholesterol levels. Material and Methods: Wild type (WT) and ApoE deficient (ApoE -/- ) mice received a normal or cholesterol-rich diet for 54 days. At day 18, experimental OA was induced by intra-articular injection of collagenase and animals were sacrificed at day 28 and 54. Results: ApoE -/- mice on a normal diet showed remarkably higher LDL levels than WT mice (8.90 mmol/L and 0.40 mmol/L, respectively; p<0.0001). Experimental OA in ApoE -/- mice showed no increase in synovial thickening and ectopic bone formation, but a significant increase of cartilage damage was found in ApoE -/- mice compared to WT mice at the lateral side of the femoral chondyle (OARSI score 13.7 and 6.8, respectively; p<0.05). Synovial gene expression of both S100A8 and S100A9 was significantly increased in ApoE -/- mice compared to WT mice (fold increase 1.8 and 1.4, respectively; p<0.05). Furthermore, S100A8/S100A9 protein levels of synovial wash-outs was increased in ApoE -/- mice at day 28 (fold increase 5.8; p<0.05), which was confirmed by immunohistochemical staining for S100A8. In addition, we investigated whether a cholesterol-rich diet could increase joint pathology after induction of OA. This diet increased differences in LDL levels even more (18.4 mmol/L in ApoE -/- mice versus 1.2 mmol/L in WT mice; p<0.0001) and already at day 28, histological differences between the two groups were observed. Synovial thickening was increased by 400% in ApoE -/- mice compared to WT mice (p<0.001) and also ectopic bone formation in the medial collateral ligament was strongly increased at this early time point (fold increase 2.7; p<0.01). Cartilage damage, however, was comparable to damage observed in mice on a normal diet. Again, S100A8 and S100A9 levels were strongly increased in ApoE -/- mice, both on protein and gene expression level and significantly correlated with ectopic bone formation. Conclusion: LDL cholesterol accumulation by ApoE deficiency results in increased S100A8 and S100A9 production by synovial cells. A cholesterol-rich diet further increases this production which correlates with increased synovial thickening and ectopic bone formation in experimental OA. This suggests a important role for LDL cholesterol in developing OA joint pathology.